2020
DOI: 10.1109/access.2020.3021904
|View full text |Cite
|
Sign up to set email alerts
|

Mastering the Working Sequence in Human-Robot Collaborative Assembly Based on Reinforcement Learning

Abstract: A long-standing goal of the Human-Robot Collaboration (HRC) in manufacturing systems is to increase the collaborative working efficiency. In line with the trend of Industry 4.0 to build up the smart manufacturing system, the collaborative robot in the HRC system deserves better designing to be more selforganized and to find the superhuman proficiency by self-learning. Inspired by the impressive machine learning algorithms developed by Google Deep Mind like Alphago Zero, in this paper, the human-robot collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…For instance, Yu et al make in [121], an analogy between a chessboard and the assembly process. The selection of moves in the chessboard are compared with the HR decision-making.…”
Section: B Schedulingmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Yu et al make in [121], an analogy between a chessboard and the assembly process. The selection of moves in the chessboard are compared with the HR decision-making.…”
Section: B Schedulingmentioning
confidence: 99%
“…Due to the intrinsic structure of this type of networks, it is proven that they are faster than typical back propagation networks when trained by a supervised learning method like in [44], [45]. Alternatively, convolutional NNs [40], [41], [57], [121] are chosen for object detection and categorization, but it is demonstrated that in the majority of cases they cannot be applied in real-time and are used with a limited number of object categories.…”
Section: B Emerging Control Issues and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-component assembly sequence planning approach to increase human-robot collaboration efficiencies was proposed by Yu, Huang, and Chang (2020). Assuming an adjustable desk as an example, the scheduling process was transformed into a chessboard-shaped planning structure that was able to complete planning significantly faster than conventional methods.…”
Section: Assemblymentioning
confidence: 99%
“…Compared with traditional featurebased approaches being more complex and time-consuming for labelling a huge amount of data, the proposed method can annotate data labels automatically by perceiving human demonstrations. In another work [135], RL with CNN architecture was leveraged to optimize the working sequence of human-robot collaborative assembly, which in turn increases the working performance of smart manufacturing systems. Some complicated learning use cases, such as robot random failure and human behaviour uncertainties, were further taken into consideration to satisfy real-world conditions.…”
Section: G Other Technical Aspectsmentioning
confidence: 99%